STRATEGY ANALYSIS OF SERVICES, SYSTEMS AND FACILITIES ON EMPLOYEE PERFORMANCE THROUGH SERVICE USER SATISFACTION AT KSOP SPECIAL BATAM - Mursal Mursal; Hidayat Hidayat; Noviyanti Noviyanti; Muammar Khaddafi; Mohammad Arief Habibie (RADJA PUBLIKA, 2022)
This study aims to analyze how the strategy between services, systems and facilities with employee performance through service user satisfaction at KSOP Special Batam. The population in the study involved 2169 employees from all SIUPAL ship agency companies and SIUPKM agencies. The sampling method is based on the Krejcie and Morgan tables as many as 327 people, questionnaires are distributed via the Google Form link with an estimated data collection period of one month, after the data is collected to be processed and analyzed further. Based on the results of hypothesis testing on all independent variables showed a significant effect on the dependent, the results of testing the value of adjusted R 2 are 0.817 which means that the independent variable of service, systems, and facilities and employee performance in general, it is able to have an effect of 81.7% of service user satisfaction, while the rest is influenced by other variables outside this research model.